Short-term responses of terpene emission rates to experimental changes of PFD in Pinus halepensis and Quercus ilex in summer field conditions - Penuelas, J.; Llusia, J. (Environmental and Experimental Botany, 1999)
The diurnal relationships of monoterpene emission with PFD and photosynthetic rates were studied in the Mediterranean trees Pinus halepensis, a terpene storing species, and Quercus ilex, a non-storing species, under summer ﬁeld conditions. At morning, midday and evening, leaves were submitted to different irradiance levels by differentially shading them. Both species emitted large amounts of monoterpenes (about 20 mg g DM1 h1 ). The most emitted terpene by P. halepensis was D 3 -carene followed by b-myrcene, a-pinene and b-pinene. The most emitted terpene by Q. ilex was limonene followed by a-pinene and b-pinene. No clear correlation to temperature was found for Q. ilex emission within the diurnal range of 21–33°C, whereas P. halepensis emissions increased with the temperature. There was no consistent link between terpene emissions and PFD or photosynthetic rates for P. halepensis but there were signiﬁcant relationships for Q. ilex. However, emissions by Q. ilex became inhibited at highest PFDs and during the course of the day when net photosynthesis decreased under summer drought. The study shows that the emission rates of both species are highly variable and that during a hot Mediterranean summer day (with limited water availability) the diurnal variation of emission is not only driven by the common light and temperature dependencies. Water stress, branch-to-branch variability and other inﬂuences must explain great part of the observed variability
Keywords: a-pinene; d 3 -carene; field conditions; limonene; pfd; photosynthetic rate; Pinus halepensis; Quercus ilex; Temperature; Terpene emission